INTEGRATION Integration Of Religion And Culture : The Syuro Porridge Tradition In The Cisaat Village Community, Ciater District, Subang Regency: INTEGRASI AGAMA DAN BUDAYA : Tradisi Bubur Syuro pada Masyarakat Desa Cisaat Kecamatan Ciater Kabupaten Subang - Nabila Fitri Rahmadina; Alifia Nabila; Nia Apriliani; Afif Nurseha; Ajat Saputra (International Journal of Education, Vocational and Social Science, 2023)
Research on the integration of religion and culture of the Porridge Syuro tradition in Cisaat Village, Ciater District, Subang Regency. This research was conducted in Cisaat Village. The goal is to find out the history, meaning and function of the Syuro porridge tradition every 10th of Muharram. This type of approach is using a type of qualitative approach. The compiler is present in the field as an instrument acting directly in collecting data from observations and being actively involved in activities. Data in the form of words were taken from local community leaders, and the additional data was in the form of documents. In implementing the author using the Observation Method, the position of the compiler here is as an Observer Participant, namely observing and participating in the field. The results of the study found that the porridge syuro tradition in Cisaat Village had religious and spiritual meanings, this had become a hereditary custom and culture. By carrying out this Bubur Syuro tradition, people can always remember the events of Prophet Noah a.s on the 10th of Muharram. The Porridge Syuro tradition has a good impact on society, namely as a means to strengthen unity and oneness, togetherness and hospitality are well maintained. With KKN students taking part in enlivening the Porridge Syuro tradition, the community was very happy because they felt helped and were able to introduce cultural traditions that are still being preserved by Cisaat Village.